Chapter 30 The role of the UN Security Council in cybersecurity International peace and security in the digital age - Tikk, Eneken (Taylor & Francis, 2020)
The Routledge Handbook of International Cybersecurity examines the development and use of information and communication technologies (ICTs) from the perspective of international peace and security. Acknowledging that the very notion of peace and security has become more complex, the volume seeks to determine which questions of cybersecurity are indeed of relevance for international peace and security and which, while requiring international attention, are simply issues of contemporary governance or development. The Handbook offers a variety of thematic, regional and disciplinary perspectives on the question of international cybersecurity, and the chapters contextualize cybersecurity in the broader contestation over the world order, international law, conflict, human rights, governance and development. This book will be of much interest to students of cybersecurity, computer science, sociology, international law, defence studies and International Relations in general.